Implementasi Corporate Social Responsibility dalam Meningkatkan Literasi Keuangan di Masyarakat - Prihastini, Cantika Putri; Indrayani, Heni (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
Abstract Fraud in investments is a problem that must be addressed immediately. The rise in cases of investment fraud has created a negative perception in society regarding investment, making people reluctant to invest. Indonesia Stock Exchange in this case implements Literacy and Education Activities Corporate Social Responsibility (CSR) In the Capital Market Sustainable Program as an effort to reduce investment fraud, because the lack of financial literacy makes people more vulnerable to being cheated. The aim of this research is to explain the implementation of literacy and educational activities Corporate Social Responsibility (CSR) capital market sustainable program carried out by Indonesia Stock Exchange is carried out on the basis of Theory of Planned Behavior (TPB). This research uses descriptive qualitative research methods with an interpretive paradigm. Primary data was obtained by conducting in-depth interviews and observations with sources. Secondary data was obtained through searches such as research journals, books and scientific writings related to this research. Data analysis through stages of data reduction, data presentation, and drawing conclusions and verification. The results of this research indicate that the implementation of literacy and education activities Corporate Social Responsibility (CSR) The Capital Market Sustainable Program carried out by Indonesia Stock Exchange is carried out on the basis of Theory of Planned Behavior (TPB) by applying attitudes (self-courage, likes challenges, high confidence, understanding of inflation,awareness good financial management, a sense of pride), Subjective Norms (investment trends, fear of missing out or FOMO, information from influencers, as well as the influence of friends), Perceived Behavioral Control (public confidence in investment), and Intention (ease of access, effectiveness of the material, and professionalism of the mentors). Keywords: Corporate social responsibility; financial literacy; investment fraud; theory of planned behavior. Abstrak Penipuan pada investasi menjadi salah satu permasalahan sosial yang harus segera ditangani. Maraknya kasus penipuan investasi menimbulkan persepsi negatif di masyarakat mengenai investasi sehingga membuat orang enggan berinvestasi. PT Bursa Efek Indonesia dalam hal ini mengimplementasikan kegiatan literasi dan edukasi Corporate Social Responsibility (CSR) Pada program berkelanjutan pasar modal sebagai upaya mengurangi penipuan investasi, karena dengan minimnya literasi keuangan mengakibatkan masyarakat lebih rentan untuk ditipu. Tujuan penelitian ini adalah untuk menjelaskan implementasi kegiatan literasi dan edukasi Corporate Social Responsibility (CSR) program berkelanjutan pasar modal yang dilakukan oleh PT Bursa Efek Indonesia dilakukan atas dasar Theory of Planned Behavior (TPB). Metode penelitian yang digunakan melalui pendekatan kualitatif deskriptif dengan paradigma interpretif. Data primer diperoleh melalui wawancara mendalam, observasi, studi kepustakaan dan dokumentasi. Data sekunder diperoleh melalui penelusuran seperti jurnal-jurnal penelitian, buku, dan tulisan ilmiah terkait dengan penelitian ini. Analisa data melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa implementasi kegiatan literasi dan edukasi Corporate Social Responsibility (CSR) program berkelanjutan pasar modal yang dilakukan oleh PT Bursa Efek Indonesia dilakukan atas dasar Theory of Planned Behavior (TPB) dengan menerapkan attitudes (keberanian diri, suka akan tantangan, kepercayaan yang tinggi, pemahaman akan inflasi, awareness yang baik terhadap pengelolaan keuangan, rasa bangga atau pride), Subjective Norms (trend investasi, sikap fear of missing out atau FOMO, informasi dari influencer, serta pengaruh teman), Perceived Behavioral Control (kepercayaan masyarakat akan investasi), dan Intention (kemudahan akses, efektifitas materi, serta profesionalisme dari pemateri). Kata-kata kunci: Corporate social responsibility; literasi keuangan; penipuan investasi; theory of planned behavior.